Evaluation of serum ferritin in in type II diabetes mellitus: a hospital based observational study from Dibrugarh, Assam, India - Borah, Meghna; Goswami, Rohini K. (International Journal of Research in Medical Sciences, 2016)
Background: Increased serum ferritin, reflecting body iron overload, is often associated with insulin resistance. The role of iron in the pathogenesis of diabetes is suggested by an increased incidence of type 2 diabetes mellitus in diverse causes of iron overload, and reversal or improvement in glycemic control) with a reduction in iron load achieved using either phlebotomy or iron chelation therapy. Methods: This study was carried out to assess Serum Ferritin levels in Type 2 diabetes mellitus and to examine whether a correlation between Serum ferritin and HbA1c% and fasting blood glucose levels exists. 92 type 2 diabetes subjects (M:F - 52:40) were studied and compared with age and gender matched controls. Results: The study showed that serum ferritin levels was significantly increased in diagnosed cases of type 2 diabetes mellitus in comparison with the age and gender matched healthy individuals (p value<0.01). A strong positive correlation was found between HbA1c% and serum ferritin levels and the correlation was found to be statistically significant (p<0.01). A strong positive correlation was also found between serum ferritin and fasting blood glucose levels Conclusions: Therefore, the findings in the present study indicates that serum ferritin was increased in diabetes as long as glycemic control was not achieved and that this increase may contribute to the pathogenesis of this disease as well as in the development of complications. Thus, routine screening for serum ferritin concentration in pre-diabetes and diabetic patients can be done to assess the body iron stores.